2009
DOI: 10.1124/dmd.109.029512
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N-Acetyltransferase 2 Polymorphism on Tumor Target Tissue DNA Adduct Levels in Rapid and Slow Acetylator Congenic Rats Administered 2-Amino-1-methyl-6-phenylimidazo[4,5-b]pyridine or 2-Amino-3,8-dimethylimidazo-[4,5-f]quinoxaline

Abstract: ABSTRACT:2-Amino-3,8-dimethylimidazo-[4,5-f ]quinoxaline (MeIQx) and 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) are suspected human carcinogens generated in well done meats. After N-hydroxylation, they are O-acetylated by N-acetyltransferase 2 (NAT2) to electrophiles that form DNA adducts. dG-C8-MeIQx and dG-C8-PhIP adducts have been identified in human tissues. In the female rat, administration of PhIP leads to mammary and colon tumors, whereas MeIQx induces liver tumors. Both humans and rats exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
3
7
0
Order By: Relevance
“…These results are consistent with colon as a tumor target organ of PhIP in rodents (Sugimura et al, 2004). Previous studies have identified PhIP-DNA adducts in rat and mouse colon (Kaderlik et al, 1994;Snyderwine et al, 2002;Metry et al, 2009), and they have also been identified in human colon (Malfatti et al, 2006).…”
Section: Resultssupporting
confidence: 79%
“…These results are consistent with colon as a tumor target organ of PhIP in rodents (Sugimura et al, 2004). Previous studies have identified PhIP-DNA adducts in rat and mouse colon (Kaderlik et al, 1994;Snyderwine et al, 2002;Metry et al, 2009), and they have also been identified in human colon (Malfatti et al, 2006).…”
Section: Resultssupporting
confidence: 79%
“…No PhIP-C8-dG adducts were detected in control animals dosed with corn oil alone. Previous studies have shown higher levels of PhIP-C8-dG adducts are detected in colon tissue when compared to the liver, which is consistent with the colon being the target tissue for tumour development [29,30].…”
Section: Discussionsupporting
confidence: 72%
“…LC-mass spectrometry has made sufficient gains in sensitivity for the detection of DNA adducts resulting in it being a viable alternative to other detection methods such as 32 P-postlabelling and immunoassays, to provide more accurate and precise results through the use of stable isotope internal standards [27,28]. Recently, LC-tandem mass spectrometry (MS/MS) methods using deuterated stable isotope internal standards and off-line pre-purification of the PhIP-C8-dG adduct using solid phase extraction or online column-switching LC have been described for the detection and quantitation of adducts in cells and DNA treated in vitro with PhIP, and also in the liver and colon of rats treated in vivo with PhIP [20,22,[29][30][31]. Mass spectrometry based methods offer a number of advantages with respect to the identification and quantitation of DNA adducts, as they rely on the detection of adduct-specific ions and characteristic transitions of the ions being monitored, respectively, and because quantification is based upon the use of isotopicallylabelled internal standards.…”
Section: Introductionmentioning
confidence: 99%
“…Tail moment is defined as the product of the tail length and the fraction of total DNA in the tail. Tail moment incorporates a measure of the smallest detectable size of migrating DNA (reflected in the comet tail length) and the number of relaxed/broken pieces represented by the intensity of the DNA found in the tail [34]. OTM in control cell populations ranged from 0.0 to 0.92 with an average of 0.155 ± 0.022 (SEM).…”
Section: Curcumin Inhibits Double-strand Dna Damage Caused By Phipmentioning
confidence: 99%
“…Previous studies have shown that PhIP induces the production of reactive oxygen species (ROS) and DNA adduct formation [6,7,15,16]. Phytochemicals like curcumin are able to inhibit DNA adduct formation [34]. We hypothesized that curcumin may be a potential food additive that may be inhibitory to PhIP-induced carcinogenicity by inhibiting ROS production, DNA adduct formation and DNA strand breaks.…”
Section: Introductionmentioning
confidence: 98%